PERAN AKUNTAN DI ERA SOCIETY 5.0 - Nurvita Sari, Silvi Indah; Latifah, Eny (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to find out the role of accountants in the Society 5.0 era. The research method is qualitative with the type of literature. The result of the research is that in the era of Society 5.0, accountants can carry out their work processes using technology (digital) so that they are completed quickly. Although the role of the accounting profession has been replaced by technology in the Society 5.0 era, the accounting profession still has new career opportunities and its role is expanding. Therefore, accountants must develop (digital) technology competencies, implement new technology prototypes (learning-by-doing process), train based on Society 5.0 programmes (digital human skills), respond to changes in industry, business, and technological developments, and international certification-based training. The limitation of this study lies in the national documents used in this study. This led to a lack of information obtained during the analysis of this research. If there is a desire to continue this research in the future, we hope to enrich the international literature and enable a comparison of the transformation of the role of accountants at each stage of Society 5.0